Ascertainment and outcomes of atrioventricular septal defects in Pietersburg Hospital, Limpopo Province, South Africa - Shibambu, Giyani Patrick (My University, 2019)
Background: Congenital heart disease (CHD) is a significant contributor to Under 5 Mortality rate(U5MR) in Limpopo. Atrioventricular septal defect (AVSD) is the best ascertained lesion in Limpopo and is strongly associated with Down syndrome. Few children from Limpopo with CHD including AVSD access cardiac diagnostic and surgical services. Objectives: The study aimed to enumerate, describe syndromes associated with AVSD and outcomes of children with AVSD at Pietersburg hospital. Methods: This is a Retrospective study of all children (n=80) diagnosed with AVSD from 1 January 2010 to 31 December 2014 at Pietersburg hospital. Data were drawn from echocardiogram reports and patient records. District Health Information Software (DHIS) data was used to obtain the number of live births per district during the 5 years study period. Results: Eight hundred and sixty six (n=866) patients had a first diagnosis of CHD confirmed on echocardiography and 80 (9.2%) of these had AVSD (an estimated 31.5% of expected cases of AVSD). Eighty four per cent (84%) of AVSD patients were associated with Down syndrome. 42/67 (63%) AVSD patients were referred for surgical assessment and of those 15/42 (36%) had surgery. The median interval between diagnosis and surgery was 13 months. Seventy five percent (n=50/67) of patients defaulted follow up. Conclusion: The study confirmed that most children with AVSD had associated Down syndrome and that the majority of children with AVSD from Limpopo do no access surgery. There is under referral of children with Down syndrome for screening of CHD.
Thesis (M. Med.(Paediatrics and Child Health)) -- University of Limpopo, 2019
Keywords: Congenital heart disease; Atrioventricular septal defect; Mortality rate; Children with Down syndrome; Congenital heart disease in children; Cardiovascular system -- Diseases -- South Africa -- Limpopo; Children with Down syndrome